GAYA HIDUP MASYARAKAT DAN MINAT BELI PAKAIAN BEKAS (THRIFT) DALAM PERSPEKTIF EKONOMI ISLAM - Nabilla Dara Kartika; Romi Adetio Setiawan; Padlim Hanif (Universitas Islam Negeri Mataram, 2024)
This research investigates the evolving lifestyle trends that have influenced consumer preferences for secondhand clothing, commonly known as “thrift.” The study aims to comprehend how lifestyle choices and costumer interests contribute to the practice of thrifting within the community, while also exploring the Islamic economic perspective on these lifestyle choices and consumer interests related to secondhand clothing utilization (thrift). Employing a qualitative research approach, the study focuses on observasing and analyzing thrifting activities at the Panorama Market in Bengkulu city as its research context. The findings reveal that lifestyle plays a pivotal role in shaping consumer interest in secondhand clothing, with community lifestyle choices exerting a positive influences on this interest. Primary factors driving this interest include affordability considerations, the reliability of product quality, alignment with fashion trends, social influence from the thrifting, community, and positive purchasing experiences. Furthermore, the Islamic economic perspetive offers valuable insights and guidance in understanding this phenomenon.